PEMEROLEHAN BAHASA ANAK MELALUI PENGUKURAN MEAN LENGTH OF UTTERENCE - Fina Mardiana Nasution (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
This research was conducted when the children were 3 years and 6 months old. The child’s nams is Muhammad Habibie. The son of Mr. Azwal Effendi and Mrs. Rostiana. This study was conducted to test the children's speaking ability in 1, 2, 3, 4 and 5 words. This study uses the average utterance length (MLU) survey method. The data collection technique was done by recording the children's spoken words using a mobile phone. The use is a tap recording method, and the recording results are written and analyzed. A method for viewing and analyzing morphemes and structures used by children. Research shows that children have poor language skills. From this the author concludes that the child cannot speak yet.